2022
DOI: 10.3390/su14148471
|View full text |Cite
|
Sign up to set email alerts
|

Is Digital Economy a Good Samaritan to Developing Countries?

Abstract: It is no surprise that the digital economy (DE) has raised expectations and it is still raising them. The aim of this study is to implement testing which will indicate how much the digital economy can help the less developed countries to overcome the economic lag. In order to come up with an answer, the study is based on provocative hypotheses which will elaborate on the development paradox by which the digital economy cannot help the less developed countries. The argument that supports the main hypothesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Aghion and Howitt (1998) argued that the rapid advancement of DE may hinder economic growth by affecting the structure of the labor market. Additionally, Yousefi (2011), Ma et al (2022b), Ishida (2015), and Lazović et al (2022) found no causal relationship between DE and economic performance. They suggested that infrastructure investment may exacerbate rather than alleviate inequality, and investment in DE might not necessarily contribute to the development of less developed countries.…”
Section: De and Economic Developmentmentioning
confidence: 85%
See 1 more Smart Citation
“…Aghion and Howitt (1998) argued that the rapid advancement of DE may hinder economic growth by affecting the structure of the labor market. Additionally, Yousefi (2011), Ma et al (2022b), Ishida (2015), and Lazović et al (2022) found no causal relationship between DE and economic performance. They suggested that infrastructure investment may exacerbate rather than alleviate inequality, and investment in DE might not necessarily contribute to the development of less developed countries.…”
Section: De and Economic Developmentmentioning
confidence: 85%
“…While DE has the potential to help address regional disparities and bridge the divide between developed and developing regions (Matkovskaya et al, 2022), it is important to note that the emergence of the information technology revolution has not only failed to promote balanced global development but has also exacerbated global inequality. This phenomenon is often referred to as the "digital divide" (Lazović et al, 2022).…”
Section: Heterogeneity Analysismentioning
confidence: 99%
“…Many published studies describe that, for developing economies, the technological development caused by Industry 4.0 can transform their previous economic development trajectory. The development based on productivity growth up to that point and parallel growing employment may be halted by digitization and automation of processes [24][25][26][27].…”
Section: The Role and Importance Of Digital Transitionmentioning
confidence: 99%
“…Developing countries work to build their digital economies. They want to take advantage of the possibilities of the digital economy for their expansion and advancement (Lazović et al 2022).…”
Section: Source Analysismentioning
confidence: 99%